Current unemployment variance decomposition and consequences of using proxies - Carlos Henrique Corseuil; Miguel Nathan Foguel; Ajax Moreira (Institute for Applied Economic Research (ipea), 2021)
We offer a decomposition for the variance of the current unemployment rate that not only measures the contributions of labor market flows but also of the approximation error embedded in other decompositions that use surrogates for the current rate. Using data for the United States and Brazil, the results for the latter show significant differences in the flows' contributions and non-negligible distortions of approximation errors when the variance of the current (instead of the proxy) rate is decomposed; for the U.S., no substantial changes are detected.
Keywords: E24; J64; 330; unemployment; labor market flows; decomposition